Synthesis and Characterization of Mono- and Bicycle Heterocyclic Derivatives Containing 1, 2,4-Triazole, 1,3,4-Thiadiazine and 1,3-Thiazole Rings - Navabeh Nami; Mehdi Forozani; Vida Khosravimoghadam; Rahmatallah Taherinasab (E-Journal of Chemistry)
Reaction of tartaric acid with thiocarbohydrazide (2) and thiosemicarbazide (6) afforded 1,2-bis(4-amino-5-mercapto-4H-1,2,4-triazol-3-yl)-ethane-1,2-diol (3) and 1,2-bis(5-mercapto-4H-1,2,4-triazol-3-yl)-ethane-1,2-diol (7). Reaction of compounds 3 and 7 with DMAD (dimethylacety lendi carboxylate) and DEAD (diethylacetylendicarboxylate) gave 1,2-bis(7-[(z)-methoxycarbonylmethylen]-5,6-dihydro-5H-6-one-[1,2,4] riazolo[3,4-b] [1,3,4] thiadiazin-3-yl)-ethan-1,2-diol (4), 1,2-bis(7-[(z)-ethoxycarbonylmethylen] -5,6-dihydro -5H-6-one-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazin-3-yl)-ethan-1,2- diol (5) and 1,2-bis(6-[(z)-methoxycarbonylmethylen]-5-oxo-[1,3]thiazolo[2,3-c] [1,2,4]triazol-3-yl)-ethan-1,2-diol (8) in good yields.